TRANSFORMASI PENDIDIKAN TASAWUF DALAM TRADISI ISLAM MELAYU DI ERA MODERNITAS - Helmi Handoko; Cukup Islamiarso; Abdullah Idi; Muhammad Abdillah Asmara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the transformation of Sufism education in the contemporary Malay Islamic tradition, focusing on the shift in methodological paradigms and the resilience of traditional values ​​amidst digitalization. Using a qualitative, descriptive-analytical approach, data were collected through participant observation, in-depth interviews with murshids and educational figures in Palembang, and a documentary study of classical manuscripts. The results demonstrate an epistemological reconstruction in which Sufism has transformed into an active and inclusive "Islamic psychotherapy" for urban communities to address psychospiritual distress. Methodologically, a hybridization of scientific transmission has occurred through the use of digital platforms (such as live streaming and podcasts) to examine authoritative texts such as Siyar al-Salikin, while maintaining the integrity of "Adab" and "Sanad" through physical interaction (muwajahah). Apart from that, Sufism education is integrated with local wisdom "Tunjung Ajar Melayu" which forms leadership characters with integrity and tawadhu. This research concludes that the transformation of Sufism education functions as a cultural filter that is able to absorb technological advances without sacrificing the identity of Malay spirituality which is based on the philosophy of "Adat bersendi syarak, syarak berndi kitabullah."